2016
DOI: 10.1371/journal.pntd.0005220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polymerase Chain Reaction (PCR) with Slit Skin Smear Examination (SSS) to Confirm Clinical Diagnosis of Leprosy in Eastern Nepal

Abstract: BackgroundDetection of Mycobacterium leprae in slit skin smear (SSS) is a gold standard technique for the leprosy diagnosis. Over recent years, molecular diagnosis by using PCR has been increasingly used as an alternative for its diagnosis due to its higher sensitivity. This study was carried out for comparative evaluation of PCR and SSS microscopy in a cohort of new leprosy cases diagnosed in B. P. Koirala Institute of health Sciences, Dharan, Nepal.Methodology/Principal FindingsIn this prospective crossectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…De Wit et al (1993) reported on the utility of PCR for detection of M. leprae in nasal swab specimens amplifying the 531-bp pra gene, demonstrating 79.6% positivity of PCR [22]. Kyeong-Han Yoon reported PCR on slit skin samples, which was subsequently reported by many others [23,24,25,26,27,28]. PCR on biopsies has been reported by Wichitwechkarn et al (1995), with a mean PCR positivity of 66% and subsequently by many others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…De Wit et al (1993) reported on the utility of PCR for detection of M. leprae in nasal swab specimens amplifying the 531-bp pra gene, demonstrating 79.6% positivity of PCR [22]. Kyeong-Han Yoon reported PCR on slit skin samples, which was subsequently reported by many others [23,24,25,26,27,28]. PCR on biopsies has been reported by Wichitwechkarn et al (1995), with a mean PCR positivity of 66% and subsequently by many others.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional PCR targeting a single gene has been found to be the most frequently reported method. Several authors have used conventional PCR on slit skin, biopsy, urine, blood [27,37,38,39,40]. On the other hand, few studies have utilized multiplex PCR on slit skin and biopsies, amplifying more than one target sequence, at the same level of laboratory settings as conventional PCR [21,26,35,41].…”
Section: Resultsmentioning
confidence: 99%
“…Eventually if untreated, leprosy leads to disability and disfigurement. Thus, early detection of M. leprae is important to timely identification and treatment of patients [2] .…”
Section: Introductionmentioning
confidence: 99%
“…For exemple, Kang et al [9] extracted DNA from the scalpel blade used for collecting bacilloscopy and found 73% positivity with RLEP primers -67.7% of samples with negative bacilloscopy presented positive PCR. Siwakoti et al [10] extracted DNA from microscope slides used for bacilloscopy, with 44% sensitivity of the PCR in PB patients.…”
Section: !mentioning
confidence: 99%